2022
DOI: 10.1097/sap.0000000000003278
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Reconstruction in Adults With Exstrophy of the Bladder

Abstract: Introduction Abdominal wall reconstruction in an adult patient with exstrophy bladder is challenging. A variety of local and regional flaps are described. We describe our experience with a 3-layer technique with the differential reconstruction of the fascial and cutaneous layer. Patient and Methods Three adult patients with untreated bladder exstrophy were included in the study period from 2017 and 2019. The surgical technique involved 3-layer abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…6 Several abdominal flaps have been described as well. 7 Ete et al 8 reported a three-layer reconstruction with good functional results. However, cases with significant pubic diastasis may be particularly challenging since this might preclude the fixation of an abdominal mesh.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several abdominal flaps have been described as well. 7 Ete et al 8 reported a three-layer reconstruction with good functional results. However, cases with significant pubic diastasis may be particularly challenging since this might preclude the fixation of an abdominal mesh.…”
Section: Discussionmentioning
confidence: 99%